Cancer cell migration depends on adjacent ASC and adipose spheroids in a 3D bioprinted breast cancer model - Horder, Hannes; Böhringer, David; Endrizzi, Nadine; Hildebrand, Laura S.; Cianciosi, Alessandro; Stecher, Sabrina; Dusi, Franziska; Schweinitzer, Sophie; Watzling, Martin; Groll, Jürgen; Jüngst, Tomasz; Teßmar, Jörg; et al. (Biofabrication, 2024)
Breast cancer develops in close proximity to mammary adipose tissue and interactions with the local adipose environment have been shown to drive tumor progression. The specific role, however, of this complex tumor microenvironment in cancer cell migration still needs to be elucidated. Therefore, in this study, a 3D bioprinted breast cancer model was developed that allows for a comprehensive analysis of individual tumor cell migration parameters in dependence of adjacent adipose stroma. In this co-culture model, a breast cancer compartment with MDA-MB-231 breast cancer cells embedded in collagen is surrounded by an adipose tissue compartment consisting of adipose-derived stromal cell (ASC) or adipose spheroids in a printable bioink based on thiolated hyaluronic acid. Printing parameters were optimized for adipose spheroids to ensure viability and integrity of the fragile lipid-laden cells. Preservation of the adipogenic phenotype after printing was demonstrated by quantification of lipid content, expression of adipogenic marker genes, the presence of a coherent adipo-specific extracellular matrix, and cytokine secretion. The migration of tumor cells as a function of paracrine signaling of the surrounding adipose compartment was then analyzed using live-cell imaging. The presence of ASC or adipose spheroids substantially increased key migration parameters of MDA-MB-231 cells, namely motile fraction, persistence, invasion distance, and speed. These findings shed new light on the role of adipose tissue in cancer cell migration. They highlight the potential of our 3D printed breast cancer-stroma model to elucidate mechanisms of stroma-induced cancer cell migration and to serve as a screening platform for novel anti-cancer drugs targeting cancer cell dissemination.
CRIS-Team Scopus Importer:2024-07-12
Keywords: 3D bioprinting; adipose tissue; adipose-derived stromal cells; breast cancer model; live-cell imaging; migration; spheroids

Collective forces of tumor spheroids in three-dimensional biopolymer networks - Mark, Christoph; Grundy, Thomas J.; Strissel, Pamela; Böhringer, David; Grummel, Nadine; Gerum, Richard; Steinwachs, Julian; Hack, Carolin; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner; O'Neill, Geraldine M.; et al. (eLife, 2020)
We describe a method for quantifying the contractile forces that tumor spheroids collectively exert on highly nonlinear three-dimensional collagen networks. While three-dimensional traction force microscopy for single cells in a nonlinear matrix is computationally complex due to the variable cell shape, here we exploit the spherical symmetry of tumor spheroids to derive a scale-invariant relationship between spheroid contractility and the surrounding matrix deformations. This relationship allows us to directly translate the magnitude of matrix deformations to the total contractility of arbitrarily sized spheroids. We show that our method is accurate up to strains of 50% and remains valid even for irregularly shaped tissue samples when considering only the deformations in the far field. Finally, we demonstrate that collective forces of tumor spheroids reflect the contractility of individual cells for up to 1 hr after seeding, while collective forces on longer timescales are guided by mechanical feedback from the extracellular matrix.
CRIS-Team WoS Importer:2020-05-22

Collective Synchronization of Contractile Forces in Tumor Spheroids - Böhringer, David; Mark, Christoph; Grummel, Nadine; Strissel, Pamela; Strick, Reiner; Grundy, Thomas J.; O'Neill, Geraldine M.; Fabry, Ben (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Correction: Collective forces of tumor spheroids in three-dimensional biopolymer networks. - Mark, Christoph; Grundy, Thomas J.; Strissel, Pamela; Böhringer, David; Grummel, Nadine; Gerum, Richard; Steinwachs, Julian; Hack, Carolin; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner; O'Neill, Geraldine M.; et al. (eLife, 2020)
EVALuna2:417751

Corrosion Resistance of Biodegradable Zinc Surfaces Enhanced by UV-Grafted Polydimethylsiloxane Coating - Pupillo, Davide; Bruns, Mark; Prado, Lucia; Di Franco, Francesco; Böhringer, David; Mazare, Anca Valentina; Goldmann, Wolfgang; Virtanen, Sannakaisa; Santamaria, Monica; Tesler, Alexander (ACS Biomaterials Science and Engineering, 2024)
Improved living conditions have led to an increase in life expectancy worldwide. However, as people age, the risk of vascular disease tends to increase due to the accumulation and buildup of plaque in arteries. Vascular stents are used to keep blood vessels open. Biodegradable stents are designed to provide a temporary support vessel that gradually degrades and is absorbed by the body, leaving behind healed blood vessels. However, biodegradable metals can suffer from reduced mechanical strength and/or inflammatory response, both of which can affect the rate of corrosion. Therefore, it is essential to achieve a controlled and predictable degradation rate. Here, we demonstrate that the corrosion resistance of biodegradable Zn surfaces is improved by electroless deposition of zinc hydroxystannate followed by UV-grafting with silicone oil (PDMS). Potentiodynamic polarization, electrochemical impedance spectroscopy, respiratory kinetic measurements, and long-term immersion in three simulated body fluids were applied. Although zinc hydroxystannate improves the corrosion resistance of Zn to some extent, it introduces a high surface area with hydroxyl units used to UV-graft PDMS molecules. Our results demonstrate that hydrophobic PDMS causes a 3-fold reduction in corrosion of Zn-based materials in biological environments and reduces cytotoxicity through the uncontrolled release of Zn ions.
CRIS-Team Scopus Importer:2024-07-26
Keywords: biodegradable metals; corrosion resistance; polydimethylsiloxane; UV-grafting; zinc

Dynamic traction force measurements of migrating immune cells in 3D biopolymer matrices - Böhringer, David; Cóndor, Mar; Bischof, Lars; Czerwinski, Tina; Gampl, Niklas; Ngo, Phuong; Bauer, Andreas; Bosch-Voskens, Caroline; Lopez Posadas, Rocío; Franze, Kristian; Budday, Silvia; Mark, Christoph; et al. (Nature Physics, 2024)
Immune cells, such as natural killer cells, migrate with high speeds of several micrometres per minute through dense tissue. However, the magnitude of the traction forces during this migration is unknown. Here we present a method to measure dynamic traction forces of fast migrating cells in biopolymer matrices from the observed matrix deformations. Our method accounts for the mechanical nonlinearity of the three-dimensional tissue matrix and can be applied to time series of confocal or bright-field image stacks. It allows for precise force reconstruction over a wide range of force magnitudes and object sizes—even when the imaged volume captures only a small part of the matrix deformation field. We demonstrate the broad applicability of our method by measuring forces from around 1 nN for axon growth cones up to around 10 μN for mouse intestinal organoids. We find that natural killer cells show bursts of large traction forces around 50 nN that increase with matrix stiffness. These force bursts are driven by myosin II contractility, mediated by integrin β1 adhesions, focal adhesion kinase and Rho-kinase activity, and occur predominantly when the cells migrate through narrow matrix pores.
CRIS-Team Scopus Importer:2024-11-29

Epithelial RAC1-dependent cytoskeleton dynamics controls cell mechanics, cell shedding and barrier integrity in intestinal inflammation - Martínez Sánchez, Luz del Carmen; Phuong Anh Ngo,; Pradhan, Rashmita; Becker, Lukas S; Böhringer, David; Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Koch, Tatyana; Thonn, Veronika; Erkert, Lena; Stolzer, Iris; et al. (Gut, 2022)
Objective Increased apoptotic shedding has been linked to intestinal barrier dysfunction and development of inflammatory bowel diseases (IBD). In contrast, physiological cell shedding allows the renewal of the epithelial monolayer without compromising the barrier function. Here, we investigated the role of live cell extrusion in epithelial barrier alterations in IBD. Design Taking advantage of conditional GGTase and RAC1 knockout mice in intestinal epithelial cells (Pggt1b (i Delta IEC) and Rac1 (i Delta IEC) mice), intravital microscopy, immunostaining, mechanobiology, organoid techniques and RNA sequencing, we analysed cell shedding alterations within the intestinal epithelium. Moreover, we examined human gut tissue and intestinal organoids from patients with IBD for cell shedding alterations and RAC1 function. Results Epithelial Pggt1b deletion led to cytoskeleton rearrangement and tight junction redistribution, causing cell overcrowding due to arresting of cell shedding that finally resulted in epithelial leakage and spontaneous mucosal inflammation in the small and to a lesser extent in the large intestine. Both in vivo and in vitro studies (knockout mice, organoids) identified RAC1 as a GGTase target critically involved in prenylation-dependent cytoskeleton dynamics, cell mechanics and epithelial cell shedding. Moreover, inflamed areas of gut tissue from patients with IBD exhibited funnel-like structures, signs of arrested cell shedding and impaired RAC1 function. RAC1 inhibition in human intestinal organoids caused actin alterations compatible with arresting of cell shedding. Conclusion Impaired epithelial RAC1 function causes cell overcrowding and epithelial leakage thus inducing chronic intestinal inflammation. Epithelial RAC1 emerges as key regulator of cytoskeletal dynamics, cell mechanics and intestinal cell shedding. Modulation of RAC1 might be exploited for restoration of epithelial integrity in the gut of patients with IBD.
CRIS-Team WoS Importer:2022-03-25

Fiber alignment in 3D collagen networks as a biophysical marker for cell contractility - Böhringer, David; Bauer, Andreas; Moravec, Ivana; Bischof, Lars; Kah, Delf-Thorge Eric; Mark, Christoph; Grundy, Thomas J.; Görlach, Ekkehard; O'Neill, Geraldine M.; Budday, Silvia; Strissel, Pamela; Strick, Reiner; et al. (Matrix Biology, 2023)
Cells cultured in 3D fibrous biopolymer matrices exert traction forces on their environment that induce deformations and remodeling of the fiber network. By measuring these deformations, the traction forces can be reconstructed if the mechanical properties of the matrix and the force-free matrix configuration are known. These requirements limit the applicability of traction force reconstruction in practice. In this study, we test whether force-induced matrix remodeling can instead be used as a proxy for cellular traction forces. We measure the traction forces of hepatic stellate cells and different glioblastoma cell lines and quantify matrix remodeling by measuring the fiber orientation and fiber density around these cells. In agreement with simulated fiber networks, we demonstrate that changes in local fiber orientation and density are directly related to cell forces. By resolving Rho-kinase (ROCK) inhibitor-induced changes of traction forces, fiber alignment, and fiber density in hepatic stellate cells, we show that the method is suitable for drug screening assays. We conclude that differences in local fiber orientation and density, which are easily measurable, can be used as a qualitative proxy for changes in traction forces. The method is available as an open-source Python package with a graphical user interface.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Biopolymer Networks; Fiber Orientation; Mechanobiology; Traction Force Microscopy

Human laryngeal mucus from the vocal folds: Rheological characterization by particle tracking microrheology and oscillatory shear rheology - Peters, Gregor; Wendler, Olaf; Böhringer, David; Gostian, Antoniu Oreste; Müller, Susanna; Canziani, Herbert; Hesse, Nicolas; Semmler, Marion; Berry, David A.; Kniesburges, Stefan; Peukert, Wolfgang; Döllinger, Michael (Applied Sciences, 2021)
Mucus consistency affects voice physiology and is connected to voice disorders. Neverthe-less, the rheological characteristics of human laryngeal mucus from the vocal folds remain unknown. Knowledge about mucus viscoelasticity enables fabrication of artificial mucus with natural properties, more realistic ex-vivo experiments and promotes a better understanding and improved treatment of dysphonia with regard to mucus consistency. We studied human laryngeal mucus samples from the vocal folds with two complementary approaches: 19 samples were successfully applied to particle tracking microrheology (PTM) and five additional samples to oscillatory shear rheology (OSR). Mucus was collected by experienced laryngologists from patients together with demographic data. The analysis of the viscoelasticity revealed diversity among the investigated mucus samples according to their rigidity (absolute G’ and G”). Moreover some samples revealed throughout solid-like character (G’ > G”), whereas some underwent a change from solid-like to liquid-like (G’ < G”). This led to a subdivision into three groups. We assume that the reason for the differences is a variation in the hydration level of the mucus, which affects the mucin concentration and network formation factors of the mucin mesh. The demographic data could not be correlated to the differences, except for the smoking behavior. Mucus of predominant liquid-like character was associated with current smokers.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Human laryngeal mucus; Oscillatory shear rheology; Particle tracking microrheology; Viscoelasticity; Vocal folds

Long-term stability of aerophilic metallic surfaces underwater - Tesler, Alexander; Kolle, Stefan; Prado, Lucia; Thievessen, Ingo; Böhringer, David; Backholm, Matilda; Karunakaran, Bhuvaneshwari; Nurmi, Heikki A.; Latikka, Mika; Fischer, Lena; Stafslien, Shane; Cenev, Zoran M.; et al. (Nature Materials, 2023)
Aerophilic surfaces immersed underwater trap films of air known as plastrons. Plastrons have typically been considered impractical for underwater engineering applications due to their metastable performance. Here, we describe aerophilic titanium alloy (Ti) surfaces with extended plastron lifetimes that are conserved for months underwater. Long-term stability is achieved by the formation of highly rough hierarchically structured surfaces via electrochemical anodization combined with a low-surface-energy coating produced by a fluorinated surfactant. Aerophilic Ti surfaces drastically reduce blood adhesion and, when submerged in water, prevent adhesion of bacteria and marine organisms such as barnacles and mussels. Overall, we demonstrate a general strategy to achieve the long-term stability of plastrons on aerophilic surfaces for previously unattainable underwater applications.
CRIS-Team Scopus Importer:2023-09-29

Measurement of Skeletal Muscle Fiber Contractility with High-Speed Traction Microscopy - Böhringer, David; Rausch, Martin; Steinmann, Martin; Schrüfer, Stefan; Schubert, Dirk W.; Haertl, Annamaria; Mark, Christoph; Fabry, Ben (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Measurement of Skeletal Muscle Fiber Contractility with High-Speed Traction Microscopy - Rausch, Martin; Böhringer, David; Steinmann, Martin; Schubert, Dirk W.; Schrüfer, Stefan; Mark, Christoph; Fabry, Ben (Biophysical Journal, 2020)
We describe a technique for simultaneous quantification of the contractile forces and cytosolic calcium dynamics of muscle fibers embedded in three-dimensional biopolymer gels under auxotonic loading conditions. We derive a scaling law for linear elastic matrices such as basement membrane extract hydrogels (Matrigel) that allows us to measure contractile force from the shape of the relaxed and contracted muscle cell and the Young's modulus of the matrix without further knowledge of the matrix deformations surrounding the cell and without performing computationally intensive inverse force reconstruction algorithms. We apply our method to isolated mouse flexor digitorum brevis (FDB) fibers that are embedded in 10 mg/mL Matrigel. Upon electrical stimulation, individual FDB fibers show twitch forces of 0.37 ± 0.15 μN and tetanic forces (100-Hz stimulation frequency) of 2.38 ± 0.71 μN, corresponding to a tension of 0.44 ± 0.25 kPa and 2.53 ± 1.17 kPa, respectively. Contractile forces of FDB fibers increase in response to caffeine and the troponin-calcium stabilizer tirasemtiv, similar to responses measured in whole muscle. From simultaneous high-speed measurements of cell length changes and cytosolic calcium concentration using confocal line scanning at a frequency of 2048 Hz, we show that twitch and tetanic force responses to electric pulses follow the low-pass filtered calcium signal. In summary, we present a technically simple high-speed method for measuring contractile forces and cytosolic calcium dynamics of single muscle fibers. We expect that our method will help to reduce preparation time, costs, and the number of sacrificed animals needed for experiments such as drug testing.
CRIS-Team Scopus Importer:2020-01-24

Plasticity of 3D Hydrogels Predicts Cell Biological Behavior - Malandrino, Andrea; Zhang, Huijun; Schwarm, Nico; Böhringer, David; Kah, Delf-Thorge Eric; Kuster, Christian; Boccaccini, Aldo R.; Fabry, Ben (Biomacromolecules, 2024)
Under 3D culture conditions, cells tend to spread, migrate, and proliferate better in more viscoelastic and plastic hydrogels. Here, we present evidence that the improved cell behavior is facilitated by the lower steric hindrance of a more viscoelastic and plastic matrix with weaker intermolecular bonds. To determine intermolecular bond stability, we slowly insert semispherical tipped needles (100-700 μm diameter) into alginate dialdehyde-gelatin hydrogels and measure stiffness, yield strength, plasticity, and the force at which the surface ruptures (puncture force). To tune these material properties without affecting matrix stiffness, we precross-link the hydrogels with CaCl2 droplets prior to mixing in NIH/3T3 fibroblasts and final cross-linking with CaCl2. Precross-linking introduces microscopic weak spots in the hydrogel, increases plasticity, and decreases puncture force and yield strength. Fibroblasts spread and migrate better in precross-linked hydrogels, demonstrating that intermolecular bond stability is a critical determinant of cell behavior under 3D culture conditions.
CRIS-Team Scopus Importer:2025-02-04

Silicone-Based Lubricant-Infused Slippery Coating Covalently Bound to Aluminum Substrates for Underwater Applications - Prado, Lucia; Böhringer, David; Mazare, Anca Valentina; Sotelo, Lamborghini; Sarau, George; Christiansen, Silke; Fabry, Ben; Schmuki, Patrik; Virtanen, Sannakaisa; Goldmann, Wolfgang; Tesler, Alexander (ACS Applied Materials and Interfaces, 2023)
Wetting of solid surfaces is crucial for biological and industrial processes but is also associated with several harmful phenomena such as biofouling and corrosion that limit the effectiveness of various technologies in aquatic environments. Despite extensive research, these challenges remain critical today. Recently, we have developed a facile UV-grafting technique to covalently attach silicone-based coatings to solid substrates. In this study, the grafting process was evaluated as a function of UV exposure time on aluminum substrates. While short-time exposure to UV light results in the formation of lubricant-infused slippery surfaces (LISS), a flat, nonporous variant of slippery liquid-infused porous surfaces, longer exposure leads to the formation of semi-rigid cross-linked polydimethylsiloxane (PDMS) coatings, both covalently bound to the substrate. These coatings were exposed to aquatic media to evaluate their resistance to corrosion and biofouling. While the UV-grafted cross-linked PDMS coating effectively inhibits aluminum corrosion in aquatic environments and allows organisms to grow on the surface, the LISS coating demonstrates improved corrosion resistance but inhibits biofilm adhesion. The synergy between facile and low-cost fabrication, rapid binding kinetics, eco-friendliness, and nontoxicity of the applied materials to aquatic life combined with excellent wetting-repellent characteristics make this technology applicable for implementation in aquatic environments.
CRIS-Team Scopus Importer:2023-07-21
Keywords: anti-biofouling; biofilms; corrosion resistance; cross-linking; lubricant-infused slippery surfaces; polydimethylsiloxane; UV-grafting

Synthetic mucus for an ex vivo phonation setup: Creation, application, and effect on excised porcine larynges - Peters, Gregor; Jakubaß, Bernhard; Weidenfeller, Katrin; Kniesburges, Stefan; Böhringer, David; Wendler, Olaf; Müller, Sarina Katrin; Gostian, Antoniu-Oreste; Berry, David A.; Döllinger, Michael; Semmler, Marion (Journal of the Acoustical Society of America, 2022)
Laryngeal mucus hydrates and lubricates the deformable tissue of the vocal folds and acts as a boundary layer with the airflow from the lungs. However, the effects of the mucus' viscoelasticity on phonation remain widely unknown and mucus has not yet been established in experimental procedures of voice research. In this study, four synthetic mucus samples were created on the basis of xanthan with focus on physiological frequency-dependent viscoelastic properties, which cover viscosities and elasticities over 2 orders of magnitude. An established ex vivo experimental setup was expanded by a reproducible and controllable application method of synthetic mucus. The application method and the suitability of the synthetic mucus samples were successfully verified by fluorescence evidence on the vocal folds even after oscillation experiments. Subsequently, the impact of mucus viscoelasticity on the oscillatory dynamics of the vocal folds, the subglottal pressure, and acoustic signal was investigated with 24 porcine larynges (2304 datasets). Despite the large differences of viscoelasticity, the phonatory characteristics remained stable with only minor statistically significant differences. Overall, this study increased the level of realism in the experimental setup for replication of the phonatory process enabling further research on pathological mucus and exploration of therapeutic options. (c) 2022 Acoustical Society of America.
CRIS-Team WoS Importer:2023-01-06